TELAAH KOMPARASI KONSEP PEMBELAJARAN MENURUT IMAM AL-ZARNUJI DAN IMAM AL-GHOZALI - Juhji, Juhji (Tarbawi, 2015)
This study is a descriptive qualitative by using a comparative analysis. The data primary data of this study are ta'lim al-muta'allim book and ayyuhal walad book. While the secondary data are on the basis of Imam al-Ghazali thoughts about education, Islamic education both classical and contemporary, and the thoughts of Moslem education figures.In this study, the data is collected by using documentation method and analyzed by intellectual biography. The comparison method were was used in for data discussion. The result of the study revealed that the concept of study and learning according to imam al-Zarnuji is a metal process.The core of learning itself is characteristic and manner shaping. Imam al-Zarnuji's learning concept stesses more on moral both for teacher and students. The interaction between students and teachers must support the ethics and moral without killing the learning creativity and dynamic. While according to imam al-Ghazali, learning is the process of soul to understand the meaning of something as an effort to shape good character in order to get closer to Allah the almighty (taqarrub). Although the learning concept according to imam al-Ghazali stresses on moral, it tends to pay extra attention toward the teachers as al-Mu'allim (knowledge transporters). A teacher must have good role or moral when he/she teaching. The comparison between learning concept and learning according to imam al-Ghazali and imam al-Zarnuji are on the basis of ontology (tauhid), epistimology (knowledge) dan aksiology (akhlaq/moral). These are sourced on al-Qur'an dan al-Hadits.